REQUIREMENTS FOR A MODERN PEDAGOGUE - Bahram Jumanazarov (American Journals, 2024)
The work of educating a person is an extremely complex process, and mature people of society have been involved in this activity since ancient times. This situation means that the education of the young generation, the content of its organization, is important in determining not only the development of the individual, but also the development of the society. If a person chooses the profession of pedagogy, then he must be fully compatible with the personality of a pedagogue and the requirements imposed on him.
Keywords: pedagogic profession, personality development, pedagogical activity, pedagogical skill, pedagogue’s duties, education, education development, education efficiency, advanced technologies.